A duplicação do cubo e a impossibilidade da solução clássica: uma proposta para ensino usando geometria analítica, descritiva e dinâmica - Jesus, Adriano Tavares de (2021)
In this dissertation we study the cube duplication problem, exposing some non-Euclidean solutions of Greek and Renaissance mathematicians. We will show an algebraic approach to explain the impossibility of duplicating a cube using the ruler and compass as instruments. We suggest two ways to implement the subject through two tutorials for construction of geometric figures related to Architas’ solution and Plato’s machine using GeoGebra.